1998
DOI: 10.1111/j.1600-0846.1998.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties and contours of aging facial skin. A controlled double‐blind comparative study of the effects of retinol, melibiose‐lactose and their association

Abstract: ROL, ME-L, and ROL-ME-L formulations improve physical properties of skin that are impaired by aging. Their activities are notably superior to those of a comparative SA formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…The biological and physical reasons underlying such controversial aspects remain obscure. They have been previously addressed in the literature Piérard-Franchimont et al, 1998). Indeed, in a global view about ageing, the present data are in line with previous findings about altered shear wave propagation in bones (Wang et al, 1983;Chen and Saha, 1987).…”
Section: Fig 2: Uniform Distribution Of the Bmi Throughout The Ages supporting
confidence: 82%
“…The biological and physical reasons underlying such controversial aspects remain obscure. They have been previously addressed in the literature Piérard-Franchimont et al, 1998). Indeed, in a global view about ageing, the present data are in line with previous findings about altered shear wave propagation in bones (Wang et al, 1983;Chen and Saha, 1987).…”
Section: Fig 2: Uniform Distribution Of the Bmi Throughout The Ages supporting
confidence: 82%
“…Piérard-Franchimont et al conducted the first controlled clinical trial with retinol and demonstrated significant improvement in fine wrinkles after 12 weeks of treatment. 57 Varani and colleagues studied 1% retinol on 53 patients with photoaged skin compared with a vehicle control. They found statistically significant histologic improvement at 7 days.…”
Section: Clinical Evidencementioning
confidence: 98%
“…Duell and colleagues (1996) demonstrated that retinol could be as effective as retinoic acid in producing ‘retinoid mediated histological changes’ (like epidermal thickening and keratinocyte proliferation), but with much less irritancy. Pierard-Franchimont and colleagues (1998) first conducted a controlled clinical trial with retinol formulation. They observed that retinol formulation resulted in significant improvement in fine wrinkles after 12 weeks of treatment.…”
Section: Retinolmentioning
confidence: 99%